The role of security management system in preventing and overcoming threats security disturbances in National Security Institutions - Yacobus Sukirno; Soerya Respationo; Erniyanti Erniyanti; Fadlan Fadlan (Goodwood Publishing, 2022)
Purpose: The purpose of this research is to find out the implementation of the security management system in preventing and overcoming the threat of Obvitnas security disturbances in order to support the country's economic stability, to find out the obstacles and efforts of the role of the security management system in preventing and overcoming the threat of Obvitnas security disturbances in order to support the country's economic stability. Research methodology: The research method used in this research is normative research method by involving analysis of legal regulations, policies, and legal instruments related to applicable laws and regulations. Results: The results showed that the implementation of the security management system in preventing and overcoming the threat of security disturbances to the National Obvitnas in order to support the stability of the country's economy, namely the implementation of the Security Management System as measured through the 5 (five) elements mentioned in Police Regulation Number 7 of 2019, has not been running optimally, as a result there are still several accidents that cause the impact of victims and the environment of the National Obvitnas. Contributions: This study provides a comprehensive analysis of the role of security management systems in preventing and overcoming threats to national security. The findings of this study can be used by security managers to develop and implement effective security management systems to safeguard national security interests. Implementation: Barriers to the implementation of a security management system in preventing and overcoming the threat of Obvitnas security disturbances to support the stability of the country's economy, namely the implementation of the Security Management System depending on the manager's request, limited resources, diverse threat complexities. And the preparation of effective policies, increased investment and resource allocation, and improved inter-agency coordination.